The evaluation as a reference of educational quality. The case of the municipality of Sopetran, Antioquia [La evaluación como referente de calidad educativa. El caso del Municipio de Sopetran, Antioquia (Colombia)] (2018)
An investigation with mixed design is presented; focus groups, documentary review, interview and classroom observation were applied in order to compare the performance in external and internal evaluations regarding classroom practices. The results showed in dispersion graphs and simple linear regression, little dependence between evaluations. Associated aspects were: lack of preparation in the design of tests, noncorrespondence of government models with the classroom experience and the contextual conditions of the rural sector. © 2018.